Interactions between asthma and the COVID-19 pandemic - Klara Iwaniszyn-Zapołoch; Anna Małek; Olga Wysokińska; Karolina Zadrożna; Krystian Cholewa; Justyna Żyga (Kazimierz Wielki University, 2022)
ABSTRACT Introduction: The COVID-19 pandemic has been accompanying us in our daily lives for more than 2.5 years and so far there are no indications that it will leave us soon. Updating information and knowledge about it is therefore still incredibly important. Sars-CoV-2 is a virus with a high affinity for the respiratory system, so it is worth tracing its correlations with one of the more common lung diseases, asthma. Patients with this disease are concerned about whether they are at risk of contracting COVID-19 more frequently and severely, whether they face a higher risk of death if infected and how the pandemic will affect exacerbations of their underlying disease. For physicians who encounter the virus on a daily basis, it is important to know how well to manage asthmatic patients if COVID-19 is confirmed in them. State of knowledge: In medicine, not everything is clear-cut. Much depends on our patient's age, condition and other comorbidities. And also on his/her adherence to medical advice, type and degree of asthma control. In this article, we will address all these aspects and summarise the current knowledge on the interplay between COVID-19 and asthma. Conclusions: With the review of recent reports collected here, it can be thought that asthma is not an independent factor for either a higher frequency or severity of COVID-19, but neither does it affect the higher risk of death with Sars-CoV-2 infection. In terms of treatment, it is important not to interrupt the current therapy and to maintain good asthma control. This is the most optimal treatment and reduces the risk of severe COVID-19. Drugs registered for the treatment of asthma are safe and, moreover, it has been suggested that corticosteroids protect against infection to some extent.